2006
DOI: 10.1007/s00436-006-0399-1
|View full text |Cite
|
Sign up to set email alerts
|

Survey for the presence of specific free-living amoebae in cooling waters from Belgian power plants

Abstract: Free-living amoebae (FLA) are distributed ubiquitously in aquatic environments with increasing importance in hygienic, medical and ecological relationships to man. In this study, water samples from Belgian industrial cooling circuits were quantitatively surveyed for the presence of FLA. Isolated, thermotolerant amoebae were identified morphologically as well as using the following molecular methods: enzyme-linked immunosorbent assay and isoenzyme electrophoresis and PCR. Thermophilic amoebae were present at ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Other studies have indicated that N. fowleri is present in lakes in Florida, Georgia, Texas, South Carolina, Illinois, and Virginia in the United States, as well as in other countries (Behets et al 2007;Huizinga and McLaughlin 1990;MacLean et al 2004;Stevens et al 1977;Sykora et al 1983;Tyndall et al 1989;Wellings et al 1997). In addition, fatalities due to PAM have occurred in healthy children and young adults who swam in fresh water lakes in Virginia (Martinez 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated that N. fowleri is present in lakes in Florida, Georgia, Texas, South Carolina, Illinois, and Virginia in the United States, as well as in other countries (Behets et al 2007;Huizinga and McLaughlin 1990;MacLean et al 2004;Stevens et al 1977;Sykora et al 1983;Tyndall et al 1989;Wellings et al 1997). In addition, fatalities due to PAM have occurred in healthy children and young adults who swam in fresh water lakes in Virginia (Martinez 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The water samples were filtered through a cellulose nitrate filter (pore size, 1.2 μm; diameter, 47 mm, Millipore (Fisher Scientific)) (Behets et al 2007;Edagawa et al 2009), and the concentration of amoebae determined following the most probable number (MPN) method (Pernin et al 1998). When 11 L was collected, 1 L and 100 mL were filtered 10 times for each volume; for the 2 L Matouba samples, 100 and 10 mL were filtered 10 times.…”
Section: Isolation Of Amoebaementioning
confidence: 99%
“…Naegleria species are ubiquitous in wet environments and have recently been identified in domestic water sources (378), cooling waters from power plants (37), and well water (48). Several novel Naegleria spp.…”
Section: Naegleria Fowlerimentioning
confidence: 99%